KAJIAN SOSIOLINGUISTIK PEMAKAIAN BAHASA INDONESIA OLEH PENUTUR ASING DALAM KONTEN VIDEO YOUTUBE - Nugroho Ponco Santoso (Universitas Ahmad Dahlan, 2018)
TThe aim of this study is to examine T the use of Indonesian by foreign speakers in Youtube video content. The research method used is descriptive qualitative with sociolinguistic approach. The data sources from this research are video creators videos on the Youtube.com networking site also known as Youtuber. The data was collected by the method of referring and ably by looking at the video of Youtuber. Youtuber selected based on customer number and audience size on each video. Data were analyzed to find code mixed form, code change, interference and language integration. The results of the study indicate that Indonesian foreign speakers are still influenced by English as well as local languages, such as Sundanese and Javanese. The use of local languages is due to the environmental influence of these Youtubers live. In addition, the emergence of regional language use is also influenced by culture. Another distinctiveness that arises is the use of taboo language by speakers either using a foreign language or regional language in the form of mentions related to sexuality.